ADAT NIKAH SEPERSUKUAN DI NAGARI LASI KECAMATAN CANDUNG KABUPATEN AGAM SUMATERA BARAT - Tika Afrimazani (JURNAL ILMU BUDAYA, 2020)
This paper explains about tribal marriage customs in the village of Lasi, Candung District, Agam Regency, West Sumatra. In Indonesia there are various kinds of customs, one of them is Minangkabau custom. In the Minangkabau tradition, it is filled with various kinds of rules, one of which is the rules for conducting marriages, the problem encountered is that it is not permissible to have one-sided marriages. In Minangkabau there are two customs that are used in the case of marriage. The first is the traditional lareh nan, the second is the custom of lareh nan bunta. Lareh nan long tradition is not permitted to conduct cohesive marriages because long lareh traditions assume that people who have the same tribe are brothers. In adat lareh nan bunta may have one-party marriages with conditions not one datuak (tribal leader). Nagari Lasi uses a long tradition, but applies only to each other (around the village). If one of the couples from outside the traditional village is no longer valid, it means that they can have a one-man marriage. In its application there are several couples who are married to one-sided marriages in the Lasi village, this can be done because the same customary practices apply, or the village uses traditional lareh nan bunta. However, if you use the traditional lareh nan long and not for mutual nagari (around the village), but applies in its entirety then a marriage can not be done united in the Lasi village.